Analisis Penokohan dan Nilai dalam Novel Anak Simfoni Persahabatan Karya Fakhri Violinist - Filaili Ainun Jariyah; Indah Puspitasari; Raras Hafiidha Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to find the values ​​contained in the novel shown through the characterization of the characters. These characterizations are related to the values ​​that occur in the lives of the characters in the novel Simfoni Persahabatan by Fakhri Violinist. This study uses a qualitative method with a structural approach that focuses on characterization and its relationship to educational values. Data were collected through document study techniques by carefully reading the novel and noting parts related to characterization, then analyzed using content analysis techniques to draw conclusions about the values ​​and messages contained in the novel. The results of the study show that the author successfully presents the characterization of two main characters, namely Nancy who has an arrogant nature and often insults others, and Bintang who is humble and always prays to God. Through the characterization of these two characters, the author conveys various educational values ​​including the value of simplicity, the spirit of pursuing ideals, moral education such as diligent study and humility, character education regarding respect for parents and teachers, the value of hard work, responsibility, patience in facing trials, the importance of admitting mistakes and forgiveness, and friendship. This research contributes to the world of education in utilizing children's literature as a medium for character formation, and provides references in selecting reading materials that suit the needs of children's character development.